Enclave to urbanity : Canton, foreigners, and architecture from the late eighteenth to the early twentieth centuries - Farris, Johnathan (Hong Kong University Press, 2016)
'Enclave to Urbanity' examines how the architecture and the urban landscape of Guangzhou framed the relations between the Western mercantile and missionary communities and the city's predominantly Chinese population. The book takes readers through three phases: the 13 Factories era from the 18th century to the 1850s; the Shamian enclave up to the early 20th century; and the adoption of Western building techniques throughout the city as its architecture modernized in the early Republic. The discussion of architecture goes beyond stylistic trends to embrace the history of shared and disputed spaces, using a broadly chronological approach that combines social history with architectural and spatial analysis.